Study on Secondary Grouting Slurry of Closed Cell Perlite for Shield. Issue 2 (May 2021) - Wen, Yongxiang; Shang, Ningning; Cui, Cancan; Kang, Shaowei; Zhou, Wei; Han, Zhongzhi; Guo, Xiaojun
Abstract: With high belite cement, sulphoaluminate cement and portland cement cement as cementing materials, closed pore perlite as aggregate and anti-washout admixtures of underwater concrete as additive, the secondary grouting slurry test of expanded perlite suitable for shield grouting was carried out. The test results show that the setting time of secondary grouting slurry of expanded perlite prepared by high belite cement is moderate, which is suitable for secondary grouting slurry preparation; the initial fluidity of slurry prepared by expanded perlite with higher bulk density and the same ratio of cementitious material to aggregate is better, and the fluidity loss is lower; when the ratio of cementitious material to aggregate is between 5:2 And 5:3, the secondary grouting slurry of expanded perlite has better secondary filling effect.